ECO-FRIENDLY BEHAVIORAL OF HIGH SCHOOL STUDENTS IN BANDUNG - Septian, Yoga Ganteng; Ruhimat, Mamat; Somantri, Lili (Jurnal Pendidikan Geografi Gea, 2017)
Bandung city has some environment problems, such as: rubbish, river, air pollution, groundwater depletion and river pollution. The government tries to make serious efforts to overcome those problems through regulations endorsement and modern technology application, but the main effort that must be done is by improving the behavior of every citizen to be more environment-friendly. Senior high school students are expected to involve in improving the environmental problems because they are the integral part of society. This research is aimed to find out the impact of various factors that influence environment-friendly behavior, such as: 1) the influence of students’ knowledge about environment-friendly behavior; 2) the influence of environmental cares attitude towards environment-friendly behavior; 3) the influence of students’ environmental knowledge towards environment-friendly behavior. The subject of this research is all senior high school students in Bandung with 200 students as the sample. And use purposive sampling as the sampling technique, and then the data is analyzed by using regression test. The result of this research shows that students’ environmental knowledge and environmental cares attitude have no effect to environment-friendly behavior. On the other hand, the environmental cares attitude is influenced by students’ knowledge about environment.